2015
DOI: 10.4172/2473-3350.1000397
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Population Genetic Diversity of Hyalinoecia tubicola (Polychaeta: Onuphidae) from the North East Coast of Tunisia (Western Mediterranean) using Random Amplified Polymorphic DNA Markers

Abstract: Journal of Coastal Zone ManagementJ o u rn al of C o a s ta l Zon e M a n ag emen t Abstract To evaluate genetic variability within and among Populations of Hyalinoecia tubicola (Müller, 1776), 30 individuals from seven populations were compared using random amplified polymorphic DNA (RAPD) markers. Populations of Hyalinoecia tubicola (Müller 1776) were sampled during the period 2005-2006 from six different sites in the Cap Bon peninsula (North East coast of Tunisia). Genomic DNA of the 25 individuals studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Most prior studies have found no or little genetic differentiation among polychaete populations (e.g. Shen and Gu 2015;Zaâbi et al 2015;David et al 2016). High levels of gene flow were inferred between populations of two polychaetes, Laenereis culveri and Capitella nonatoi, living in lagoons in Brazil, albeit with there being evidence of somewhat restricted gene flow between particular populations (Seixas et al 2018).…”
Section: Resultsmentioning
confidence: 88%
“…Most prior studies have found no or little genetic differentiation among polychaete populations (e.g. Shen and Gu 2015;Zaâbi et al 2015;David et al 2016). High levels of gene flow were inferred between populations of two polychaetes, Laenereis culveri and Capitella nonatoi, living in lagoons in Brazil, albeit with there being evidence of somewhat restricted gene flow between particular populations (Seixas et al 2018).…”
Section: Resultsmentioning
confidence: 88%
“…Zaâbi et al (2015) present evidence of possible cryptic species within Hyalinoecia tubicola in Tunisia.…”
Section: Checklistsmentioning
confidence: 78%